An Analysis on the Students’ Mastery in Using Preposition in, on, at - Wida Rianti,et.al (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research to analyze of students’ mastery in using preposition (in, on and at) and also concerned the problems faced for students’ mastery on using preposition (in, on and at). This research used qualitative research. The writer chose the Eleventh Grade students of SMKN 1 Bangkinang kota. The respondents are 36 students. Based on the result of the test, the writer conclude that the profile of students’ mastery such as: 3 students out of 36 students the level of preposition mastery is “good” and the percentage is 8,3%, 11 students or out of 36 students is “enough” and the percentage 30,5%, 21 students or out of 36 students is “poor” and the percentage is 58,3%, and 1 students or out of 36 students is “Failed” and the percentage is 2,7%”. The problems faced of students’ mastery are: the students confused to answer the question on using preposition (in, on, and at). They do not understand the differences of each preposition. Because it has similar meaning. Which explain the time and place. Students are less concerned when they to use in, on or at because they think it is less attention when talking directly. The problem that is caused by the language transfer. In contrary, this study concern with that rules. And they usually used generalization or ordinary usage without saw the context of sentence.